The insulin activity model based on insulin profiles - Nowicki, Tomasz (Journal of Computer Sciences Institute, 2019)
The purpose of the research was to propound an insulin activity model in a human body after a subcutaneous injection. A deterministic model in the form of a mathematical function was formulated. The research was based on pharmaceutic publicly available drug information published by the manufactures. The paper presents in detail the model. The obtained results can be used in computer simulations of diabetes mellitus therapy. They suggest that activity models may be assigned to types of insulin instead of separate products.